Children's practices of ICT and social inequalities : on the uses of the Magalhães computer in two school communities - Silva, Pedro (2017)
This paper addresses the Portuguese government measure that introduced a laptop - the Magalhães computer - in primary education as an attempt to extend the social base of the use of ICT. It tries to give an account of family adhesion to this computer, of some of its uses by children in different contexts, and of the question of inequality in opportunities and uses of ICT. It was based on two studies conducted in schools from two towns in different Portuguese regions. Their methodological design took a longitudinal stance and included a quantitative strand through a survey with teachers, parents and children, as well as a qualitative strand through interviews with teachers and parents and the ethnography of a class in each setting. Data revealed a) a strong adhesion to the Magalhães; b) its regular use by children (mainly at home, secondly, at school, and, thirdly, in other contexts), predominantly under their own initiative; c) the existence of a greater proportion of other computers at home by families with a higher degree of education; d) a more frequent and widespread use of the Magalhães at home by children of parents with a higher degree of education; e) a significantly uneven family support, which is stronger in socially advantaged groups; and f) less imposing rules on the use of the Magalhães at home by families with less education. Data suggest a double trend: a) a widespread acquisition of the Magalhães; and b) a selective use of the computer by the different social groups, accompanied by family mediation that is also selective. This means that, although the first political goal of the programme has apparently been fulfilled, it still lacks the next step, which addresses the effects of the socially differentiated uses of ICT at school and at home.